Child's Play - Holland, Tom.; Vincent, Alex.; Brad Dourif; Chris Sarandon; Dinah Manoff; Jack Colvin; Tommy Swerdlow; Catherine Hicks (USA United Artists, 1988)
When serial killer Charles Lee Ray is mortally wounded in a police shoot-out, he uses a voodoo spell to transfer his soul into Chucky, a ""Good Guys"" doll. Andy receives the doll as a birthday gift, and Chucky soon resumes his killing spree. However, Charles doesn't want to be trapped in the body of a doll forever. His only escape would be to transfer into the first human he revealed his true identity to... which places Andy in mortal danger.
Young Andy Barclay gets the doll he wanted. However, he did not know it was alive!
Don Mancini
Language(s): English, French Subtitle(s): English, French
Keywords: Thriller; Horror